STUDI BIDANG BARU STANDARDISASI TERMASUK ICT DENGAN PENDEKATAN PERTUMBUHAN STANDAR INTERNASIONAL IEC DAN STANDAR NASIONAL SNI - Waluyo, Prihadi (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Standardization have moved rapidly following the development of science and technology and the need of trade. So that, to facilitate trade and to protect domestic consumers, we need supply or standards appropriately, such as study of new area of standardization with international standard and SNI development approach. The determination of priority of new area of standardization to be done by analysis the standards growth, use the same ICS, compare with the growth of international standards (ISO & IEC) versus SNI. The growth is measured by the growth curve slope during year 1991-2007, with slope more than 50% is meant high. Several new area of standardization from the study include Information technology, Sinematography, Radiation, and medical laboratorium science.